The terminator [videorecording (Blu-Ray)] - Cameron, James, 1954-; Schwarzenegger, Arnold; Hamilton, Linda, 1956-; Paxton, Bill; Winfield, Paul (20th Century Fox Home Entertainment, 2013)
An indestructible cyborg-a Terminator-is sent back in time to kill Sarah Connor, the woman whose unborn son will become humanity's only hope in a future war against machines.